eDNA offers opportunities for improved biodiversity monitoring within forest carbon markets - Michael C. Allen; Julie L. Lockwood; Rosa Ibanez; Josh D. Butler; Jordan C. Angle; Benjamin D. Jaffe (Communications Earth & Environment)
Abstract Forest-based carbon sequestration projects incentivize reforestation and restoration activities while offering opportunities to realize co-benefits such as biodiversity conservation. While conservation aspects are increasingly emphasized in these projects, the rigor of biodiversity co-benefit verification has been highly variable. Recent advances in biodiversity monitoring based on shed DNA in the environment (eDNA) offer promise for improving effectiveness, standardization, and transparency. Here we analyze 129 forest carbon projects and 396 peer-reviewed studies to identify how biodiversity co-benefits are currently verified within forest carbon markets, and to evaluate the potential of eDNA for tracking biodiversity change. Our analysis revealed that eDNA studies focused more on smaller organisms (microbes and invertebrates) and on temperate ecosystems compared with biodiversity-focused forest carbon projects. Efforts to align these two worlds via investments into broadening the geographic and taxonomic scope could allow greater adoption and increased accountability in biodiversity monitoring within forest carbon markets (i.e. standardized, auditable biodiversity data trails). Adapting advancements in eDNA technology to the biodiversity monitoring needs of nature-based initiatives will aid countries and organizations striving to meet global conservation commitments.